Det felaktiga folket : Svenska kyrkans roll i försvenskningen av kvänerna 1840–1950 - Fjällborg, Anna (Linköpings universitet, Institutionen för kultur och samhälle, 2024)
This thesis is about the Assimilation Policy against the minority Kvens in the years 1840-1950. The purpose of this thesis is to investigate which role the Church of Sweden played in the assimililation and what made bishops and priests to take this role. The base is the theoretical concepts of nation and nationalism, identity and etnicity, minority and majority and authority. This study is mainly a collocation of previous research. In november 2023, the Swedish state finished a commissionwork about the Assimilation Policy against the Kvens and gave an account for the discrimination, excesses and assimilation from the state and the Church of Sweden against the Kvens. (SOU 2023:68) That work is the main source in this thesis. During the investigated period, the church was intertvined with the state which made it a part of the nationalistic endeavor to make every person in Sweden a good citizen and a good Evangelic-Lutheran Christian. The church contributed in coercive methods such as language compulsion to teach every person Swedish, Racial biology and Eugenics and to make the Kvens change place for worship. The only approved language in both the state and the church was Swedish and this enforced the Kvens to learn a new language and stop using their own minority language Meänkieli. It started with the children, but with time every Kven was affected by the Assimilation Policy. The Religious Revivial movement the Laestadianism became a safe haven for the Kvens because during their services Meänkieli was allowed. Thanks to the Laestadianism the Kvens could continue to meet Kvens in Finland and Norway in a transnational community. Both the Swedish state and the Church of Sweden felt treatened by this transnational community which they feared was a threat to the nation and the homogenization. The church became a part of the nationalistic struggle to make Sweden strong and independent. Both the state and the church believed in "one nation–one language–one church". A strong nation was homogenous with all citizens ...